Extraperitoneal pediatric kidney transplantation of adult renal allograft using an en-bloc native liver and kidney mobilization technique - Mahmoud Alameddine; Joshua S. Jue; Mahmoud Morsi; Javier Gonzalez; Marissa Defreitas; Jayanthi J. Chandar; Jeffrey J. Gaynor; Gaetano Ciancio (BMC, 2020)
Abstract Background We describe the safety and efficacy of performing pediatric kidney transplantation with a modified extraperitoneal approach that includes mobilization of the native liver and kidney. Methods We retrospectively identified pediatric renal transplants performed using this technique between 2015 and 2019. Data on patient demographics, surgical technique, and intraoperative details were collected. Outcomes were measured by morbidity and re-operation at 90 days, as well as serum creatinine, allograft survival, and overall survival at 1 year. Results Twenty-one patients with a median age of 5 (IQR 3-9) years, weighing 17.5 (IQR 14.5-24) kg were included. Median donor age was 24 (IQR 19-31) years. No intraoperative complications occurred. One child required a right native nephrectomy to allow sufficient space. Postoperatively, all patients had immediate graft function without urine leak or allograft thrombosis. 90-day morbidity and re-operation rates were zero. Both 1-year allograft and overall survival were 100% (on follow-up of all 21 patients through 1 year post-transplant), with a median serum creatinine of 0.58 (IQR 0.47-0.70) mg/dl at 1 year post-transplant. Conclusions Pediatric kidney transplantation of adult renal allografts using an extraperitoneal approach with native liver and kidney mobilization has promising allograft and patient survival outcomes that eliminates peritoneal violation and may diminish the need for native nephrectomy.